Impact of a 3-weeks specific sport rehabilitation cycle on neuromotor control in professional soccer players with lower limb injuries before return-to-play - Memain, G.; Yiou, E.; Carling, C.; Fourcade, P.; Bouvet, J.; Maille, P.; Tamalet, B. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: During the last decade, professional soccer players (PSP) have been exposed to increased amount of stress on their musculoskeletal apparatus due to the greater volume and intensity of football demands1. Despite prevention strategies, the frequency and severity of injuries hasn`t decreased2. As such, evaluating progression during rehabilitation and return-to-play (RTP) programmes3 and specifically neuromotor control is crucial in limiting the risks of re-injury4. This study aimed to investigated the effect of a 3-week specific sport rehabilitation (SSR) program on neuromotor control PSP with lower limb injuries. METHODS: Altogether, 15-male PSP suffering from various unilateral lower limb injuries (chondropathy, muscle lesions, anterior crucial ligament rupture) and 22 uninjured PSP (UPSP) participated. All performed 3 unilateral countermovement jumps (CMJ) with each leg ; before and after a SSR program3 for injured participants and during a single session for healthy participants. Movement analyses included whole-body kinematics, kinetics and lower limb muscle activation. Main variables were: peaks of trunk flexion and lateroflexion, knee flexion, peak and mean of %maximal voluntary contraction of studied muscles, rate of force development (RFD), peak of vertical ground reaction force , reactive strength index modified, jump height and movement time. A limb symmetry index (LSI, % difference between injured and non-injured leg) and a deficit limb index (DLI, % difference between injured leg and dominant leg of healthy participants) were computed for each variable. RESULTS: All CMJ variables significantly improved following the SSR program (p<0.05). Improvements ranged between +7% (RFD) and +26% (jump height). LSI applied to each CMJ variable almost reached 100% after SSR, indicating a quasi-equivalent performance level between healthy and injured leg. Despite the improvement, CMJ variables except eccentric and early concentric RFD were lower in injured PSP than in healthy participants (p<0.05 to p<0.001). DI applied to each CMJ variable showed that CMJ performance remained lower in injured than in healthy participants. CONCLUSION: The neuromotor control of injured PSP significantly improved following 3-week SSR program. However when CMJ variables were compared post SSR program to normative values in UPSP, it appeared that recovery was incomplete. These results suggest that a longer SSR program is necessary to ensure safe RTP, and that DLI seems to be more relevant than LSI for decision-making during RTP programs.